One-pot two-step synthesis of alkyl levulinates directly from furfural by combining Ni3Sn2 alloy nanoparticles and montmorillonite K10. Issue 22 (18th October 2022) - Yamanaka, Nobutaka; Abe, Daiki; Miwaka-Saiga, Masaiku; Yasunaga, Kenji; Yamada, Hiroshi; Shimazu, Shogo
Abstract : In this work, we developed a catalytic system comprising Ni3 Sn2 alloy nanoparticles and montmorillonite K10 that is effective for the one-pot two-step synthesis of alkyl levulinates directly from furfural. Abstract : In this work, we developed a catalytic system comprising Ni3 Sn2 alloy nanoparticles and montmorillonite K10 that is effective for the one-pot two-step synthesis of alkyl levulinates directly from furfural. Ni3 Sn2 alloy nanoparticles quantitatively reduced furfural to furfuryl alcohol in various alcohol solvents, namely methanol, ethanol, 1-propanol, 2-propanol, and 1-butanol, under H2 atmosphere. Three types of clay minerals, that is, kaolinite, halloysite, and montmorillonite K10, were applied in ethanol solvent for the alcoholysis of furfuryl alcohol to the corresponding alkyl levulinate, namely ethyl levulinate, under N2 atmosphere. Their catalytic performances followed the order of montmorillonite K10 > halloysite > kaolinite, consistent with that of their Brønsted acidities. After the quantitative synthesis of furfuryl alcohol by Ni3 Sn2 alloy nanoparticles in the alcohol solvents, montmorillonite K10 was added to each reaction system to produce the corresponding alkyl levulinates through the alcoholysis of the in situ formed furfuryl alcohol. Consequently, various alkyl levulinates were obtained in moderate to good yields of up to 71%.